Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Chrysidoidea, Dryinidae - Olmi, Massimo (Zootaxa, 2020)
An updated checklist of the Arabian species of Dryinidae is provided here. The list includes 40 identified species in eight genera and five subfamilies: Anteoninae (2 genera, 11 species), Aphelopinae (1 genus, 4 species), Bocchinae (2 genera, 5 species), Dryininae (1 genus, 5 species) and Gonatopodinae (2 genera, 15 species). Distributions, both on the Peninsula and extra-limital, are provided for each species; nine species (23%) are endemic to the Arabian Peninsula.